Pengembangan LKPD Berbasis Discovery Learning pada Materi Perubahan Wujud Zat Kelas IV UPTD di SDN Pejagan 1 - Carryna Zalfa Ainia; Bagus Rahmad Wijaya (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Science learning on the topic of changes in the states of matter in elementary schools requires teaching materials that actively engage students in constructing knowledge through direct observation, experimentation, and concept discovery. However, the student worksheets commonly used in classrooms mainly consist of practice questions and have not optimally facilitated students' active participation in the learning process. Therefore, this study aimed to develop a Discovery Learning-Based Student Worksheet (LKPD) for Grade IV students at UPTD SDN Pejagan 1. The study employed a Research and Development (R&D) approach using the 4D model, consisting of the Define, Design, Development, and Disseminate stages. The validity of the developed LKPD was evaluated by teaching material, material, and instructional design experts, while its practicality and effectiveness were assessed through limited and implementation trials involving teachers and students. The validation results demonstrated that the LKPD achieved scores of 83.33% from teaching material experts, 78.84% from material experts, and 95% from instructional design experts, indicating that the product met the validity criteria. Practicality testing showed excellent results, with teacher observation scores increasing from 97% in the limited trial to 100% in the implementation trial, while student observation scores improved from 93% to 95%, reflecting the ease of use and successful implementation of the LKPD in classroom learning. Furthermore, the effectiveness evaluation revealed 100% classical learning mastery in both trials, accompanied by highly positive student responses of 94% and 96%, indicating that the LKPD successfully enhanced student engagement, supported concept discovery, and facilitated meaningful learning experiences. These findings demonstrate that the Discovery Learning-Based LKPD is valid, practical, and effective for supporting science learning on changes in the states of matter in elementary schools.